2016
DOI: 10.1186/s12884-016-0807-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors associated with early initiation and frequency of antenatal care (ANC) visits in a rural and urban setting in South Africa: a cross-sectional survey

Abstract: BackgroundLate booking and infrequent antenatal care (ANC) are common but avoidable patient-related risk factors for maternal deaths in South Africa. The aim of the study was to examine the association of psychosocial factors with early initiation of ANC and adequate frequency of attendance of ANC clinics among women in an urban and rural location in South Africa.MethodsData from a 2006 cross-sectional household survey of 363 women from the rural Western Cape and 466 women from urban Gauteng provinces of South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
53
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 34 publications
12
53
4
Order By: Relevance
“…Nearly all women in the sample (96%) reported attending an antenatal clinic, and close to half (49%) did so within the first trimester. These findings are consistent with other studies of antenatal care initiation in South Africa which indicate that almost all women receive antenatal care during pregnancy (35), but a significant proportion delay seeking care beyond the first trimester (3638) which increases the risk of adverse pregnancy outcomes (39). Most women in the sample attended more than four antenatal visits during their most recent pregnancy which is similar to the Western Cape average of 4.7 visits (35) and WHO guidelines (33).…”
Section: Discussionsupporting
confidence: 91%
“…Nearly all women in the sample (96%) reported attending an antenatal clinic, and close to half (49%) did so within the first trimester. These findings are consistent with other studies of antenatal care initiation in South Africa which indicate that almost all women receive antenatal care during pregnancy (35), but a significant proportion delay seeking care beyond the first trimester (3638) which increases the risk of adverse pregnancy outcomes (39). Most women in the sample attended more than four antenatal visits during their most recent pregnancy which is similar to the Western Cape average of 4.7 visits (35) and WHO guidelines (33).…”
Section: Discussionsupporting
confidence: 91%
“…A study conducted in Southern and Northern areas of China suggested the same finding with our study [15]. The proportions of having adequate prenatal visits, receiving the first prenatal visit within 12 weeks and delivering at secondary- or higher-level health facilities in our study were higher than those in other developing countries such as Ethiopia and Africa, and were also higher than those of previous studies reported in Shaanxi Province and Western China [8, 1621]. This suggested that the coverage of maternal health services utilization has been improved after years of development, which is consistent with the result of a study comparing the inequality status of maternal health services utilization before and after health care reform in Shaanxi Province[11].…”
Section: Discussionsupporting
confidence: 88%
“…While attention has focused on physical changes and discomfort during pregnancy, far less has been paid to women’s emotional, economic, and social well-being [40], especially in African settings [but see 13,14,30,41, 42]. In women’s narratives, a dominant theme was that pregnant women at times felt vulnerable and emotionally alone, and sometimes were unable to identify what was bothering them or had no one with whom to discuss what was going on in their lives [40,43].…”
Section: Discussionmentioning
confidence: 99%